Religious changes and cultural transformations in the early modern western Sephardic communities - Kaplan, Yosef (Studies in Jewish history and culture, 2019)
From the sixteenth century on, hundreds of Portuguese New Christians began to flow to Venice and Livorno in Italy, and to Amsterdam and Hamburg in northwest Europe. In those cities and later in London, Bordeaux, and Bayonne as well, Iberian conversos established their own Jewish communities, openly adhering to Judaism. Despite the features these communities shared with other confessional groups in exile, what set them apart was very significant. In contrast to other European confessional communities, whose religious affiliation was uninterrupted, the Western Sephardic Jews came to Judaism after a separation of generations from the religion of their ancestors. In this edited volume, several experts in the field detail the religious and cultural changes that occurred in the Early Modern Western Sephardic communities.